Fusion of IDC Operation Support System Design and Analysis - Huazhao Liu; Xuefeng Chen; Qian Yu (Dianxin kexue)
By the establishment of IDC space, network, cloud computing various levels of resource element model, fusion process, data, operation and service, a standard, and loosely coupled IT support fusion architecture was designed and built, which laid the foundation for IDC intensive operation. On the basis of depth study of the IDC resource model, service mechanism and characteristics of products, IDC resources centralized control system and multi-wave cross domain construction scheduling process were designed. The application of IDCIMS in IDC intensive operation was focused on.